THE ROLE OF PROJECT-BASED LEARNING IN DEVELOPING SPEAKING SKILLS AMONG SECONDARY SCHOOL STUDENTS - Talapova A.K.; Abay G. (Progress in Science, 2025)
This article investigates the effectiveness of Project-Based Learning (PBL) in improving speaking skills among secondary school students learning English as a foreign language. The study draws on constructivist and sociocultural principles emphasizing collaborative learning and real-world communication. Fifty-two students aged 13–16 from a secondary school in Almaty participated in a six-week intervention in which speaking-centered projects were integrated into English lessons. Data were collected through pre- and post-intervention questionnaires, peer-assessment rubrics, and teacher observation checklists. Results demonstrated significant improvement in students’ speaking fluency, vocabulary range, and confidence, along with increased motivation and participation. The findings support the implementation of PBL as an effective instructional method for fostering oral communication skills in EFL classrooms